Acknowledging and addressing real-world challenges to treating immune-related adverse events - Bonnie L Bermas; Mitchell S von Itzstein; David E Gerber; Alexa Meara (Journal for ImmunoTherapy of Cancer)
Immune checkpoint inhibitors (ICIs) have revolutionized oncology treatment. However, their success is mitigated by the recognition that ICI-induced immune-related adverse events (irAEs) pose considerable challenges to patients and clinicians. These autoimmune toxicities are heterogeneous, unpredictable, and reflect a disease state resulting from a change in the immune system of patients. This contrasts with the typical acute nature of toxicities from chemotherapy and molecularly targeted oncology therapies. Management is further complicated by the extended bioavailability of these agents in patients as well as the persistence of autoimmune pathology. Currently, irAE treatment remains suboptimal in many areas, as many expert guidelines remain vague on the optimal selection, dosing, and duration of steroids and the use of other immunosuppressive agents. This coupled with delays in diagnosis and difficulties for patients accessing effective irAE treatment results in barriers to effective irAE care. The latter is complicated by the lack of US Food and Drug Administration-approved irAE treatments that lead to insurance denials, as well as the high cost of biological immunosuppressant therapies. Fortunately, rheumatologists and other subspecialists with expertize in the management of chronic autoimmune conditions have become more involved in irAE diagnosis and management and may help navigate treatment. In this commentary, we discuss these issues and propose potential solutions to advance the field.